Dynamics of nanowire shape evolution - Soon, Casey Min Liang. (2009)
When a macroscopic metallic wire is subject to a perturbation, it will neck down to its most stable shape. Different nanowires with radii comparable to the Fermi Wavelength display remarkably different behavior. We model the nanowire into 2 shapes for analysis, namely the typical cylinder and the “sine” shape model. We experiment the difference in energy functional and the mesoscopic electron-shell potential which occurs as a perturbation is applied to the nanowire. Using Mathematica to help us solve these complex problems, we are able to generate accurate approximations based on certain conventional theories. We study the different parameters affecting the shape of the nanowires in this evolutionary state. We also discover the parameters of the nanowire that affects its stability. We are able to set a perturbation, in the form of a sine shape, to a typical cylindrical nanowire. We study how the dynamics of the shape evolution affect the behavior of the nanowires under a small perturbation in certain constraints. Using theories from the quantum mechanics and the typical conventional energy theories, we will explain the shape evolution of the nanowires.